The Effect of Internal Control on Fraud in Village Fund Management with Accountability as a Mediation Variable - Muhammad Femas Hardyansyah; Eko Wahjudi (Al-Qalam Institue, 2026)
This study aims to examine the effect of internal control on fraud in public fund management and to investigate the mediating role of accountability in this relationship. An explanatory quantitative research design was employed using a total sampling technique involving 45 public officials responsible for fund management. Primary data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with WarpPLS 7.0 to evaluate both direct and indirect relationships among the variables. The findings demonstrate that internal control has a significant effect on fraud, while also significantly enhancing accountability. In addition, accountability significantly influences fraud and serves as a significant mediating variable in the relationship between internal control and fraud. These results indicate that strengthening internal control systems promotes higher accountability among public officials, which in turn contributes to reducing the risk of fraudulent practices in public fund management. The study provides empirical evidence supporting the importance of integrating robust internal control mechanisms with accountability practices to improve governance quality. The findings offer practical implications for policymakers and public sector administrators by emphasizing the need to reinforce internal control frameworks and accountability systems as strategic instruments for preventing fraud and promoting transparent, accountable, and sustainable financial governance.